PENGARUH KONSENTRASI KEPEMILIKAN, UKURAN PERUSAHAAN, DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUKARELA - Nuryaman, Nuryaman (UI Scholars Hub, 2009)
The backgroundphenomena o fthis study is thefact that low disclosure practice on the financial reporting. The objectives o f the research are to fin d out empirical evidence o f the effect o f ownership concentration, firm s size, and corporate governance mechanisms on voluntary disclosure. The corporate governance mechanisms o f this research are composition o f board o f commissioner and audit quality. Audit quality were measure by industry specialize audit firm. This study is explanatory research. The samples are on purposive samping method, and in conformity with the follow ing criteria: (a) the annual report ended 31 December 2005; (b) book value o f equity is positive. There were 101 manufacturing companies listed in Indonesia Stock Exchange. The research hyphotesis were tested using multiple regression analysis. The result o f this research show that: (1) ownership concentration has significantly positive influence on voluntary disclosure; (2) firm s size has significantly positive influence on voluntary disclosure; (3) composition o f board o f commissioner has no influence on voluntary disclosure; (4) audit quality, significantly and positively influenced voluntary disclosure.